Synthesis, structure and Hirshfeld surface analysis of 2-oxo-2H-chromen-6-yl 4-tert-butylbenzoate: work carried out as part of the AFRAMED project - Patrice Kenfack Tsobnang; Eric Ziki; Soso Siaka; Jules Yoda; Seham Kamal; Adam Bouraima; Ayi Djifa Hounsi; Emmanuel Wenger; El-Eulmi Bendeif; Claude Lecomte (Acta Crystallographica Section E: Crystallographic Communications, 2024)
In the title compound, C20H18O4, the dihedral angle between the 2H-chromen-2-one ring system and the phenyl ring is 89.12 (5)°. In the crystal, the molecules are connected through C—H...O hydrogen bonds to generate [010] double chains that are reinforced by weak aromatic π–π stacking interactions. The unit-cell packing can be described as a tilted herringbone motif. The H...H, H...O/O...H, H...C/C...H and C...C contacts contribute 46.7, 24.2, 16.7 and 7.6%, respectively, to its Hirshfeld surface.